The Dialectic Of Ethiopian Unity - Mindaralew, Zewdie (NAS RA)
This research is meant to show the philosophical secrets lying behind the persevering stance of Ethiopian unity despite the mounting negative factors that has been in force since the downfall of the Dergue regime in 1991. The attempt to uncover the philosophical underpinnings that can explain the saddeningly amazing bitter fact that Ethiopian unity somehow holds onto its existential unit in the face of a relentless, structural and intentional acidic factors being strewn unto it in the hands of the Ethiopian People’s Revolutionary Democratic Front (EPRDF) government would rely on the theoretical framework of Hegelian dialectic. To the success of this philosophical research, I helped myself profoundly to the rational and critical methods that are touted as the warps and woofs of a philosophical treatise and research. Following the hefty and strict application of the aforementioned methods coupled with the theoretical framework of analysis the Hegelian dialectic offers, I arrived at the conclusion which holds: The dismantling of cancerous and utterly divisive legal ideological and structural threats the EPRDF government has been serving for nearly three decades against Ethiopian unity stands as the total negation or antithesis of Ethiopian unity; an antithesis which gave birth to its own negation instead of dismantling into smithereens Ethiopian unity. Hence, we do have this time around the Hegelian negation of negation which comes in the form and name locally known as Fanno.
Keywords: Ethiopian unity; Hegelian dialectic